2020
DOI: 10.3390/cancers12103059
|View full text |Cite
|
Sign up to set email alerts
|

EQD2 Analyses of Vaginal Complications in Exclusive Brachytherapy for Postoperative Endometrial Carcinoma

Abstract: Background: To evaluate whether EQD2(α/β = 3Gy) at 2 cm3 of the most exposed area of the vagina is related to late vaginal toxicity in postoperative endometrial cancer (PEC) patients (p) treated with exclusive brachytherapy (BT). Methods: From 2014 to 2017, 43p were included in this study. BT was administered: 3-fractions of 6Gy in 37p and 2-fractions of 7.5Gy in 6p. The dose was prescribed at a depth of 5 mm from the applicator surface with dose-point optimization based on distance. The active treatment lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Hence, we hypothesized that considering the vagina as an OAR, EQD 2 cm 3 values of vagina could be designated as a predictor of vaginal toxicity. On analyzing the correlation of dose with toxicity in postoperative patients treated with HDR BT, we found that there was an association between EQD2 (α/β=3 Gy) at 2 cm 3 of vagina and G2 late vaginal toxicity [13][14][15]. A dose limit of 68 Gy EQD2 (α/β=3 Gy) at the most exposed 2 cm 3 of the vagina has been applied for reducing vaginal toxicity since 2016.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we hypothesized that considering the vagina as an OAR, EQD 2 cm 3 values of vagina could be designated as a predictor of vaginal toxicity. On analyzing the correlation of dose with toxicity in postoperative patients treated with HDR BT, we found that there was an association between EQD2 (α/β=3 Gy) at 2 cm 3 of vagina and G2 late vaginal toxicity [13][14][15]. A dose limit of 68 Gy EQD2 (α/β=3 Gy) at the most exposed 2 cm 3 of the vagina has been applied for reducing vaginal toxicity since 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving combined treatment, EQD2 (α/β=3 Gy) of EBRT was added to the EQD2 (α/β=3 Gy) VBT dose. The procedure of CTV definition and dose prescription has previously been reported [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring inside an applicator instead of in organs at risk (OAR) offers the main and important advantage of greatly reducing the uncertainty of the PSD probe position because the movement of OAR does not affect the PSD signal measurement. The cylinder was inserted in the vagina in the operating room and secured with elastic bands as reported elsewhere by our group [ 20 , 21 ]. The CT images provide confirmation of good contact of the applicator with the vaginal-cuff and are also the image set for 3D treatment planning with the criteria of vaginal toxicity [ 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cylinder was inserted in the vagina in the operating room and secured with elastic bands as reported elsewhere by our group [ 20 , 21 ]. The CT images provide confirmation of good contact of the applicator with the vaginal-cuff and are also the image set for 3D treatment planning with the criteria of vaginal toxicity [ 21 , 22 , 23 , 24 ]. All the patients were treated with one of the following two schemes: (a) one session of 7 Gy after external brachytherapy or (b) two fractions of 7.5 Gy in exclusive brachytherapy.…”
Section: Methodsmentioning
confidence: 99%